KEPEMIMPINAN TRANSFORMASIONAL MEMODERASI PENGARUH KOMPETENSI DAN KEDISIPLINAN TERHADAP KINERJA GURU (STUDI PADA GURU SMK NEGERI SUB RAYON 01 SEMARANG) - 11.52.02.0136, Bambang Prayitno (Jurnal Mahasiswa Pasca Sarjana, 2013)
The purpose of this study is to examine and analyze the effect of Transformal Leadership, Competence, Work Discipline on Teacher Performance, Leadership Transformal influences that act as a moderator variable relationships Teacher Competency and Performance Leadership influence and effect as a moderator variable relationship Transformal Work Discipline and Performance teacher in state vocational high school in sub rayon 01 Semarang. The population in this study was 247 teachers, while the number of respondents is 144 samples or teacher in state vocational high school in sub rayon 01 Semarang.Methods of data collection using a questionnaire with a Likert scale in the range of 1-7, and the data used are primary data or data obtained from respondents answers to the questionnaire. A statistical technique used is multiple linear regression analysis.The results showed that the Teacher Competency positive and significant effect on the performance of teachers, discipline and significant work has a positive effect terrhadap teacher performance, Kepemimmpinan Transformational positive and significant impact on teacher performance, Transformational Leadership moderate (strengthen) the effect of the Teacher Performance Competency, Transformational Leadership moderate (weaken) the relationship between the Performance Work Discipline Master. Transformational Leadership, Competence, Work Discipline, transformational leadership role in moderating the relationship Competency and Performance Teacher, Transformational Leadership in Work Discipline moderate the relationship and teacher performance together can explain the variation in teacher performance state vocational high school in sub rayon 01 Semarang was 56.2%, the rest explained by other factors not examined in this study. Keywords: Leadership Transformal, competence, work discipline and Teacher Performance